Development of Interactive Media for Hybrid Motor System in Strengthening Industrial Skills in Vocational High School - Sanatang; Wahyudi; Yahya, Muhammad (Jurnal MediaTIK, 2024)
The development of hybrid motor technology is currently one of the competencies that students must master in the automotive spectrum at Vocational High Schools (SMK), the current engine work system has developed rapidly towards the use of a combination of automotive technology and electronic technology, while learning equipment is still very limited to simple media and does not support mastery of competencies quickly and precisely. This media students can be more interactive in understanding hybrid motors. Hybrid is a type of vehicle that uses a combination of engines, resulting in significant fuel savings. Based on the description above, an Applied Research Scheme for Media Development of Hybrid Motor Working Systems Based on Industrial Learning is proposed. This research aims to produce learning media in the form of a hybrid motor working system trainer to support automotive practicum learning that can be operated and observed by students to increase students' understanding and knowledge, one of which is in the development of current vehicles. In addition, this research also developed a trainer introduction guidebook and jobsheet to make it easier for students to do practicum. This research uses the research and development method with the output in the form of a hybrid motor working system trainer in supporting students' understanding of the working system. The research and development steps used are the ADDIE model which consists of Analysis, design, development, implementation and evaluation. Based on the data, it can be concluded that the internet of things-based robotics trainer media that has been developed meets the valid criteria, the average practical aspect of the application is 91.67%, the appearance is 95.83%, the content is 91.67% and the language is 91.67%, so it can be concluded that the hybrid motor trainer media is in the very practical and effective category in its use with an N-Gain value of 0.77 or in the high category.